Design of polysaccharidic Aloe vera gel incorporated PVA/tetracycline electrospun cell culture scaffolds for biomedical applications. (16th July 2022) - Allafchian, Alireza; Fathi, Mohammad; Jalali, Seyed Amir Hossein
Abstract: In this study, hybrid nanofibrous 3D scaffolds containing Aloe vera (AV), polyvinyl alcohol (PVA) and tetracycline hydrochloride (TCH) are fabricated by electrospinning for cell culture applications. The role of polysaccharides present in AV gel is found to enhance the biocompatibility of the nanofibrous scaffolds. Different combinations of the polymers were selected to produce homogenous nanofibers with favorable mean fiber diameter and tensile strength. The surface morphology of the products was studied by SEM and it is found that the mean fiber diameter is decreased to about 188 nm upon addition of the AV component. The electrospun scaffolds were investigated by FT-IR spectroscopy to reveal the chemical structure of the samples and their crystallinity was studied by XRD. The hydrophilicity of the scaffolds was tested by optical contact angle measurements and their mechanical strength was examined by tensile strength tests. It is found that PVA is the main component contributing the mechanical stability of the scaffold structure. The fabricated scaffolds presented a more pronounced inhibitory effect against Gram-positive bacterial strains of S. aureus and B. cereus . Cell culture experiments using fibroblast L929 murine cells reveals that the AV/PVA/TCH scaffolds are promising for cell growth and the cells are capable of achieving a proper cell adhesion and proliferation. The cell viability experiment by MTT assay exhibits the contributing role of AV gel to L929 cell viability on the AV/PVA/TCH scaffolds.